Substrate preference and settlement behaviour of the megalopa of the invasive crab Percnon gibbesi (Decapoda, Percnidae) in the Mediterranean Sea. Issue 1 (January 2017) - Zenone, Arturo; Badalamenti, Fabio; Giacalone, Vincenzo; Musco, Luigi; Pipitone, Carlo; Vega Fernández, Tomás; D'Anna, Giovanni
Abstract The transition from a planktonic to a benthic life is a critical phase in which sub-adults are particularly exposed to the risk of predation and dispersion into unsuitable habitats, and plays a crucial role in the distribution, structure and dynamics of marine populations. Settlement involves the selection of an adequate substrate that provides shelter and food during early life stages.Percnon gibbesi is an alien brachyuran crab that has invaded the Mediterranean, where it is preferentially associated to boulders covered with shallow algal turf. The mechanisms of substrate selection leading to the settlement of megalopae are still unknown inP. gibbesi, yet their knowledge may shed light on its high invasiveness. We examined the substrate preference and settlement behaviour of 36 megalopae ofP. gibbesi using three natural substrates in an experimental mesocosm: gravel, cobbles and flat stones. Video recordings of 30-min trials were used to assess the substrate preference, measure the time to selection and observe the behaviour of the megalopae. Strong preference was given to hard and stable substrates i.e., cobbles and flat stones with interstices where to hide, which are also the most suitable as they provide shelter and food. Direct selection was the dominant behaviour followed by exploration and lastly by hesitation. The megalopae selected quickly the most suitable substrate to settle, likely enhancing their chances of survival. Our findings suggest that rapid settlement on a suitable substrate contributes to the success of the biological invasion ofP. gibbesi along the Mediterranean coasts.